2021
DOI: 10.21037/apm-2021-01
|View full text |Cite
|
Sign up to set email alerts
|

Narrative review of home care for palliative patients in general practice

Abstract: The need of palliative care is constantly growing worldwide and the spectrum of patients and diseases, leading to the need of palliative care is very broad (1). According to recently published data in the "Letter for National Palliative Care Advocates to send to government lead on Universal Health coverage, and UN negotiations" (2) by 2060, an estimated 48 million people (47% of all deaths globally) will die each year with serious health-related suffering, and 83% of these deaths will occur in low-income and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…However, home care also has its drawbacks. Previous studies have reported challenges related to delivering urgent care when necessary 10 and difficulties in securing staff. 11 Further, it cannot be denied that there may be a risk of COVID‐19 infection due to frequent visits from health workers, families, and relatives.…”
Section: Discussionmentioning
confidence: 99%
“…However, home care also has its drawbacks. Previous studies have reported challenges related to delivering urgent care when necessary 10 and difficulties in securing staff. 11 Further, it cannot be denied that there may be a risk of COVID‐19 infection due to frequent visits from health workers, families, and relatives.…”
Section: Discussionmentioning
confidence: 99%